The Effect of Work Stress and Work Motivation on Employee Performance at CV. Gatriec Engineering Consultan in Tasikmalaya City - Fahma Siti Laya Fajrin; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to deterimine the effect of work stress and work motivation on employee performance at CV. Gatriec Engineering Consultant in Tasikmalaya City. The method used is a quantitative method with a research sample of 40 respondents who are an employee at CV. Gatriec Engineering Consultant in Tasikmalaya City. The data is used primary data and secondary data. The analitytical tool in this research is path analysis using by SPSS version 25. The result showed that Work Stress has a direct negative effect and insignificant on Employee Performance. Work Motivation has a direct positive effect and significant on Employee Performance. Work Stress has a direct negative effect and insignificant on Employee Performance through the Work Motivation. Work Motivation has a direct positive effect and significant on Employee Performance through the Work Stress